Enhancing hepatocellular carcinoma therapy with DOX-loaded SiO2 nanoparticles via mTOR-TFEB pathway autophagic flux inhibition - Huanyu Chen; Jun Liu; Zhichao Cao; Jiajia Li; Hong Zhang; Qianqian Yang; Jian Cheng; Yuxian Shen; Kewu He (Journal of Nanobiotechnology)
Abstract Chemotherapeutic drugs often fail to provide long-term efficacy due to their lack of specificity and high toxicity. To enhance the biosafety and reduce the side effects of these drugs, various nanocarrier delivery systems have been developed. In this study, we loaded the anticancer drug doxorubicin (DOX) and an MRI contrast agent into silica nanoparticles, coating them with pH-responsive and tumor cell-targeting polymers. These polymers enable the carrier to achieve targeted delivery and controlled drug release in acidic environments. This integrated diagnostic and therapeutic strategy successfully achieved both the diagnosis and treatment of liver cancer. Additionally, we demonstrated that the nanocarrier inhibits autophagic flux in liver cancer cells by targeting the autophagy-lysosome pathway and regulating the nuclear translocation of TFEB, thereby promoting tumor cell death. This novel diagnostic-integrated nanocarrier is expected to be a promising tool for targeted liver cancer treatment.